Analysis Of Water Balance Of Corn (Zea Mays) In Bandar Lampung - Muamar, Muamar; Triyomo, Sugeng; Tusi, Ahmad; Rosadi, Bustomi (The University of Lampung, 2012)
Indonesia needs of the community against corn continues to increase with increasing population growth as well. One effort to support the increased productivity of corn agribusiness development program is the provision of adequate water for plant growth. This aims of the research were (1) calculate the amount of corn crop water requirements, (2) quantify the potential of rainwater that can be utilized and stored, (3) analyze the potential evapotranspiration, percolation and runoff rate, (4) to calculate Kc plants. Field experiment was conducted at the Integrated Field Laboratory College of Agriculture, University of Lampung from 26 August to 4 December 2011. Field observations carried out on two experimental treatment with four repettition, the treatment were plots with plastic liner (plot A) and without plastic liner (plot B) where are each equipped with a water storage pond at the downstream. The results showed that (1) The consumptive use (ETc) during the study water requirements of corn is 614,3 mm. (2) Total runoff that occurs on a plot with plastic liner adn without plastic liner of land is 58,96 mm and 37,24 mm. (3) Percolation that occurred during the study in the plot of land without plastic liner is 40,58 mm. (4) The corn crop coefficient (Kc) on average in the early developmental stages, vegetative stage, stage of flowering and seed formation, and aging stage were 1,26; 1,72; 1,66 and 1,02. (5) the water productivity on plot A was 1,88 kg/m3 while on the plot B was 2,48 kg/m3. Keywords: water balance, corn, evapotranspiration, percolation, surface runoff.